Issues in Islamic management: theories and practices - Mohd. Israil, Khaliq Ahmad (IIUM Press, International Islamic University Malaysia, 2011)
Islamic management is an emerging discipline that deals with the management of organizations and nations from the perspective of the knowledge acquired from the revealed and other Islamic sources, and results in applications compatible with the spirit of Islam. The present book provides the readers a number of research papers on Islamic management contributed by renowned scholars from around the world. The contributors have deliberated on the concepts, issues, processes, and future challenges that this new discipline of management confronts. Specifically, the papers have dealt with Corporate Governance, Leadership and Motivation, Human Resources Management and Entrepreneurship issues – all from Islamic Perspectives.